1995
DOI: 10.1002/pen.760350302
|View full text |Cite
|
Sign up to set email alerts
|

Screw optimization of a co‐rotating twin‐screw extruder for a binary immiscible blend

Abstract: The effect of the screw configuration of a closely intermeshing co‐rotating twin‐screw extruder on residence time and mixing efficiency was studied for an uncompatibilized immiscible PA6/PP (80:20) bend. Alternative screw configurations were investigated systematically. The residence time distribution (RTD) was found to be a poor indicator of the total mixing efficiency, whereas the mixing intensity function yielded considerably better information. High shear stress, sufficient residence time, and high fill ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
9
0
3
Order By: Relevance
“…A Figura 5 apresenta curvas de distribuição de tempo de residência, para uma rotação de 200 rpm e taxa de alimentação de 10 Kg/h, obtidas pela téc-nica aqui proposta comparadas às obtidas por espectroscopia de infravermelho, técnica experimental comum na literatura [19] . A primeira curva foi obtida segundo a metodologia proposta neste trabalho utilizando-se como traçador o concentrado vermelho.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A Figura 5 apresenta curvas de distribuição de tempo de residência, para uma rotação de 200 rpm e taxa de alimentação de 10 Kg/h, obtidas pela téc-nica aqui proposta comparadas às obtidas por espectroscopia de infravermelho, técnica experimental comum na literatura [19] . A primeira curva foi obtida segundo a metodologia proposta neste trabalho utilizando-se como traçador o concentrado vermelho.…”
Section: Resultsunclassified
“…Também têm sido utilizadas cargas minerais do tipo microesferas de vidro, quantificadas por análise termogravimétrica [15] , dióxido de titânio, microesferas de vidro e carbonato de cálcio determinado por atenuação ultra-sônica [16,17] e cargas metálicas do tipo flocos de alumínio utilizados em EVA e quantificados por dissolução e extração em clorofórmio [18] . Poucos traçadores com características de absorção na região do infravermelho têm sido usados sendo um deles o tiocianato de potassio KSCN que pode ser quantificado pela sua absorção a 2056 cm -1 [19] . Poucos trabalhos utilizam a absorção de luz na região do visível como detetores empregando negro de fumo como traçador em polipropileno [20] .…”
Section: Tipos De Traçadoresunclassified
See 1 more Smart Citation
“…Since 1992, several different research groups have described investigations [76,[138][139][140][141][142][143][144][145][146][147]. It has been found that when one phase is predominant the disperse phase in a polymer blend system evolves from a pellet usually to a lacelike sheet and then filaments and ultimately to droplets [76,147].…”
Section: Morphology Development For Reactive Blendsmentioning
confidence: 99%
“…In an extruder, the effect of screw configuration on residence time and mixing efficiency was studied for an immiscible PA6/PP blend. RTD was used to indicate the total mixing efficiency, and its association with the dispersion of minor phase [9]. The mechanism of fiber fracture and methods to reduce it through process improvement and machine design in fiber reinforced composites were studied by Karthik Ramani et al It is found that the residence time, fill-up, and the intensity of mixing during extrusion compounding have a predominant effect on fiber fracture [10].…”
Section: Introductionmentioning
confidence: 99%